HUBUNGAN EKSTRAKURIKULER KADER DAI DENGAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SMA MUHAMMADIYAH 01 MEDAN - Afif Syaifullah Permana Tarigan; Soiman Soiman; Zulkipli Nasution (CV. Denasya Smart Publisher, 2026)
The Islamic Religious Education Cadre (DAI) extracurricular activities are religious development activities outside of school hours that aim to enhance students' understanding of Islamic teachings and hone their da'wah skills. These activities include rhetoric training, Islamic studies, discussions, and worship practices, aimed at developing religious character and improving student learning outcomes in Islamic Religious Education (PAI). This study aims to analyze the implementation of DAI Cadre extracurricular activities, assess student learning outcomes in PAI, and identify the relationship between involvement in these activities and their academic performance. The method used was quantitative with a descriptive approach, where data were collected through questionnaires and analyzed using simple linear regression. The results indicate a positive relationship between participation in DAI Cadre extracurricular activities and improved student learning outcomes. Students who actively participate in these activities tend to have a better understanding of PAI and demonstrate improvements in cognitive, affective, and psychomotor aspects. Thus, DAI Cadre extracurricular activities can be a supporting factor in improving the quality of religious education in schools.